Evaluation of the Implementation of Sustainable UI/UX Principles in Environmental Awareness Applications: A Case Study of the Plasticpay App - Hagyana Allyssa Salwa; Intan Sartika Eris Maghfiroh; Buce Trias Hanggara; Almira Syawli (Faculty of Computer Science Universitas Indonesia, 2026)
Plastic bottle waste remains a critical issue in Indonesia. Plasticpay application encourages people to deposit plastic bottle through Reverse Vending Machines and Drop Box. Since its release, Plasticpay has received various criticisms related to interface quality and user experience. To improve the user experience, improvements are made not only focus on usability but also the implementation of sustainable UX principles to ensure efficient in using digital resources. This study aims to evaluate Plasticpay in implementing sustainable UX principles and provide interface design recommendations using mixed method with data collection through a heuristic evaluation to identify problems and a questionnaire to measure user perceptions using a 1-5 Likert scale based on sustainable UX principles. The results show that the application has been quite good in implementing sustainable UX principles, although several problems were found. Given these problems, recommendations for improvements were made to improve user experience while supporting sustainable UX implementation.